Water in the collective imagination of all ages and various cultures - Frega G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
Water is life with rich symbolism emphasizing the various aspects of these two elements. But no international Statement recognizes water as a common heritage of humanity. Water is indeed a social resource and consequently a basic common heritage for all human communities. These truths are found in the order of Nature itself, the varieties to be found therein and which bears an original characteristic print, interpreted by all those variously qualified to investigate it. So no aspect of reality, no attribute is insignificant, since this reality contains the whole deposit of all experimental facts, which can take into account certain aspects of things outside the single scientific perspective.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)